Decadal variations in the global atmospheric land temperatures. Issue 11 (10th June 2013) - Muller, Richard A.; Curry, Judith; Groom, Donald; Jacobsen, Robert; Perlmutter, Saul; Rohde, Robert; Rosenfeld, Arthur; Wickham, Charlotte; Wurtele, Jonathan
Abstract: [1] Interannual to decadal variations in Earth global temperature estimates have often been identified with El Niño Southern Oscillation (ENSO) events. However, we show that variability on time scales of 2–15 years in mean annual global land surface temperature anomalies T avg are more closely correlated with variability in sea surface temperatures in the North Atlantic. In particular, the cross‐correlation of annually averaged values of T avg with annual values of the Atlantic Multidecadal Oscillation (AMO) index is much stronger than that of T avg with ENSO. The pattern of fluctuations in T avg from 1950 to 2010 reflects true climate variability and is not an artifact of station sampling. A world map of temperature correlations shows that the association with AMO is broadly distributed and unidirectional. The effect of El Niño on temperature is locally stronger, but can be of either sign, leading to less impact on the global average. We identify one strong narrow spectral peak in the AMO at period 9.1 ± 0.4 years and p value of 1.7% (confidence level, 98.3%). Variations in the flow of the Atlantic meridional overturning circulation may be responsible for some of the 2–15 year variability observed in global land temperatures. Key Points: The Atlantic Multi‐decadal Oscillation influences Earth surface temperatures. Atlantic Meridional Overturning may be important in global climate. The AMO plays a role as important as that of ENSO.